Different frequencies of RIP among early vs. late ascospores of Neurospora crassa - Michael J. Singer; Elena A. Kuzminova; Alison Tharp; Brian S. Margolin; Eric U. Selker (Fungal Genetics Reports, 1995)
We have noticed that the frequency of RIP can be quite variable, even in crosses of the same strains. One possible source of variability is the time at which ascospores are harvested. We reasoned that the earliest ascospores shot from a perithecium might contain DNA that went through relatively few mitotic divisions in pre-meiosis. RIP occurs between fertilization and premeiotic DNA synthesis (Selker et al. 1987 Cell 51:741-752). Thus, early spores might have less exposure to RIP than late spores. Since all ascospores from a perithecium are thought to arise from a single fertilization event, a minimum of 7- 10 divisions are required to account for the number of ascospores normally produced (Perkins and Barry, 1977 Adv. Genet. 211:541-544). It is likely, however, that some ascospore lineages contain fewer divisions than others.